A clinical decision support system for chronic pain management in primary care: usability testing and its relevance. Issue 3 (1st July 2015) - Nair, Kalpana; Malaeekeh, Raheleh; Schabort, Inge; Taenzer, Paul; Radhakrishnan, Arun; Guenter, Dale
Abstract : Background: Clinical decision support systems (CDSSs) that are integrated into electronic medical records may be useful for encouraging practice change compliant with clinical practice guidelines. Objective: To engage end users to inform early phase CDSS development through a process of usability testing. Method: A sequential exploratory mixed method approach was used. Interprofessional clinician participants (seven in iteration 1 and six in iteration 2) were asked to 'think aloud' while performing various tasks on the CDSS and then complete the System Usability Scale (SUS). Changes were made to the CDSS after each iteration. Results: Barriers and facilitators were identified: systemic; user interface (most numerous barriers); content (most numerous facilitators) and technical. The mean SUS score was 81.1 (SD = 12.02) in iteration 1 and 70.40 (SD = 6.78) in iteration 2 ( p > 0.05). Conclusions: Qualitative data from usability testing were valuable in the CDSS development process. SUS scores were of limited value at this development stage.